Teaching Pancasila Education in Elementary Schools to Maintain Pancasila Ideology in the Era of Globalization - Purba, Hasnah Nurhayati (International Journal of Students Education, 2024)
This study aims to explore the role of Pancasila Education teaching in elementary schools in maintaining the Pancasila ideology in the era of globalization. With the increasing influence of foreign cultures, it is important to internalize the values of Pancasila so that the younger generation can build a strong national character and identity. The method used in this study is library research . research ), which involves collecting and analyzing data from various literature sources, including books, scientific journals, and related documents. The results of the study indicate that the implementation of Pancasila values can be done through various interesting learning methods, such as deliberation activities, flag ceremonies, and social activities. However, this study also identified challenges faced, such as students’ attitudes that are difficult to advise and the negative influence of bad habits outside of school. The conclusion of this study confirms that strengthening Pancasila education in elementary schools is very important to shape students’ character as a quality generation of the nation’s successors. Therefore, cooperation between families, schools, and communities is needed to create an environment that supports the teaching of Pancasila values effectively.